Imine‐linked covalent organic frameworks: Recent advances in design, synthesis, and application - Tianhong Huang; Weifeng Zhang; Shuai Yang; Liping Wang; Gui Yu (SmartMat)
Abstract Covalent organic frameworks (COFs) are new porous organic materials made of organic building blocks precisely constructed by strong covalent bonds. These new materials feature tunable structure, permanent porosity, high crystallinity, high specific surface area, and excellent stability, which enable COFs to be used in many applications. Linkage chemistry is a key factor in the synthesis of COFs and the control of their physicochemical properties. The boroxine, boronate‐ester, imine, hydrazone, imide, and C=C linkages have been widely used in the construction of COFs. Among the various linkages, imine has become the most important linkage for the COFs due to the easy formation of imine linkage with structural and functional diversity. Over the past decade, imine‐linked COFs have made significant progress and become an indispensable part of various applications of COFs. Here, we aim to provide a comprehensive review of the research progress in the field of imine‐linked COFs, especially the advances in topology design and COF powder and film preparation, and their important advances in gas adsorption, catalysis, and optoelectronic devices. Finally, we discuss the challenges in the design, synthesis, and application of imine‐linked COFs, and present our views on the further development of imine‐linked COFs.